A photocatalytic purification diatomite functional decorative board and preparation method thereof

By using heat-sensitive epoxy resin binder, carbon fiber web and TiO2/paraffin/alumina composite particles on the diatomaceous earth functional decorative panel, and coating the UV cured resin protective layer, the problems of insufficient mechanical strength and uneven distribution in the combination of diatomaceous earth and TiO2 are solved, and efficient photocatalytic and environmental adaptability are achieved.

CN118832947BActive Publication Date: 2025-03-07山东凯大新型材料科技有限公司

Patent Information

Application Number
CN202410815203.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-24
Publication Date
2025-03-07
Estimated Expiration
2044-06-24

AI Technical Summary

Technical Problem

In actual applications, the combination of existing diatomaceous earth and TiO2 has problems such as insufficient mechanical strength, uneven distribution of TiO2, poor performance of traditional curing methods in temperature fluctuating environments, and limited protection of UV curing resins for ultraviolet and waterproofing properties.

Method used

The thermally sensitive epoxy resin binder and carbon fiber mesh are used to uniformly coat the TiO2/paraffin/alumina composite particles, and the carbon fiber mesh is laid on it, and finally the UV cured resin is coated as a protective layer. Through these steps, the mechanical strength, photocatalytic performance and environmental adaptability of the composite material are significantly improved.

Benefits of technology

It significantly improves the mechanical strength and photocatalytic performance of the diatomaceous earth functional decorative panel, enhances its stability and durability under different environmental conditions, extends its service life, and improves the air purification efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004907378490000101
    Figure BDA0004907378490000101
Patent Text Reader

Abstract

The invention discloses a photocatalytic purification diatomite functional decorative board and a preparation method thereof, and relates to the technical field of diatomite decorative boards. The technical solution is to provide a diatomite substrate, and polish the surface with sandpaper; uniformly coat a layer of heat-sensitive epoxy resin adhesive on the diatomite substrate; lay a carbon fiber mesh on the uncured heat-sensitive epoxy resin layer, and then spread TiO2 / paraffin / alumina composite particles, and compact them with a roller, and accelerate curing with an oven; and coat the board with UV curing resin as a weather-resistant protective layer, and use a UV lamp to cure. The invention significantly improves the distribution and fixation of the composite particles of the diatomite board by applying the carbon fiber mesh and the heat-sensitive epoxy resin adhesive, and enhances the mechanical strength and photocatalytic efficiency. The carbon fiber mesh and alumina in the structure increase the wear resistance, optimize the TiO2 distribution, and improve the air purification efficiency and thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of diatomite decorative plates, and in particular to a photocatalytic purification diatomite functional decorative plate and a preparation method thereof. Background Art

[0002] Photocatalytic technology, especially the use of titanium dioxide (TiO2) as a photocatalyst, has been widely studied and applied in the fields of air purification, self-cleaning surfaces and antibacterial coatings. TiO2 is considered to be one of the most effective photocatalysts due to its excellent photocatalytic performance, chemical stability and non-toxicity. With the increasing severity of environmental pollution problems, photocatalytic technology has shown great potential in environmental management and improving indoor air quality. In addition, diatomaceous earth has been developed for the preparation of support or carrier materials to enhance the application effect of photocatalysts due to its high porosity and good water absorption.

[0003] Although the combination of diatomaceous earth and TiO2 is advantageous in theory, there are several significant deficiencies in practical applications. First, the physical strength of diatomaceous earth substrates is generally insufficient to withstand the mechanical stress that may be encountered in long-term use, especially in applications with larger areas. In addition, although TiO2 has excellent photocatalytic properties, its uniform distribution and effective fixation on diatomaceous earth substrates remains a technical challenge. Uneven distribution can lead to localized deficiencies in photocatalytic activity, affecting the overall purification effect. At the same time, traditional curing and bonding methods perform poorly in terms of environmental adaptability, especially in environments with large temperature fluctuations. Common adhesives may not be able to effectively adapt to temperature changes, resulting in peeling or damage between material layers.

[0004] The UV-curable resins used in current technologies can provide some protection from the outside world, but their protection against UV radiation and water resistance is still limited. These protective layers may degrade under long-term exposure to harsh environmental conditions, thereby reducing the service life and photocatalytic efficiency of the decorative panels.

[0005] In view of the above problems, there is an urgent need to develop a new type of diatomite functional decorative board that can not only provide a long-lasting photocatalytic purification effect, but also have higher stability and environmental adaptability in physical and chemical properties. In particular, a decorative board that can maintain stable performance under different environmental conditions is needed, and the production process of such a board should be simplified to reduce production costs and improve production efficiency. In addition, it is also necessary to improve the mechanical strength and durability of the board so that it can be used in a wider range of application scenarios, including outdoor environments that may face physical wear. Ultimately, the development of such a decorative board will help promote the application of photocatalytic technology in the fields of architecture and interior design, and provide an effective tool for improving air quality and environmental quality. In summary, in the face of current technological limitations, the development of a new decorative board that combines an improved diatomite substrate and a high-efficiency photocatalytic composite material will have significant practical application value and market potential. Summary of the invention

[0006] In order to achieve the above-mentioned invention objectives and address the above-mentioned technical problems,

[0007] The present invention provides a method for preparing a photocatalytic purification diatomite functional decorative plate, the method comprising the following steps:

[0008] A1 provides a diatomaceous earth substrate and polishes the surface with sandpaper;

[0009] A2 uniformly coats a layer of heat-sensitive epoxy resin adhesive on the diatomite substrate;

[0010] A3 lays the carbon fiber mesh on the uncured heat-sensitive epoxy resin layer, then spreads the TiO2 / paraffin / alumina composite particles, compacts them with a roller, and uses an oven to accelerate the curing;

[0011] A4: coating the plate in step A3 with UV curable resin as a weather-resistant protective layer, and curing it using a UV lamp.

[0012] Preferably, the preparation method of the diatomite substrate is as follows: 80-90 parts of diatomite powder are mixed with 10-20 parts of cellulose, 50-60% of the total weight of the mixture of water is gradually added to the mixture to obtain a wet mixture, the wet mixture is poured into a mold, the mold thickness is 5-10 mm, and the mixture is compacted at a pressure of 5 MPa using a press, and the pressure is maintained for 5 minutes. The formed plate is dried at room temperature until the surface is no longer wet, and then transferred to an oven to remove moisture, and dried at an oven temperature of 50°C for 24 hours.

[0013] Preferably, the preparation method of the heat-sensitive epoxy resin adhesive is as follows: the epoxy resin is mixed with acetone at a concentration of 4-6 g / ml, poly N-isopropylacrylamide (PNIPAM) is added to the mixture of the epoxy resin and acetone at a content of 4-6% by mass of the mixture, and stirring is continued until it is completely dissolved and evenly distributed, and 0.8-1.2% by mass of diphenyl disulfide (DMPA) is added to the above mixture, and stirring is continued to ensure complete and even distribution, and the mixture is placed in a vacuum degassing machine for degassing to remove all bubbles in the mixture, and the degassing time is 30 minutes.

[0014] Preferably, the coating thickness of the heat-sensitive epoxy resin adhesive is 0.5 mm.

[0015] Preferably, the epoxy resin is bisphenol A type epoxy resin.

[0016] Preferably, in step A3, TiO2 nanoparticles are dispersed using anhydrous ethanol and then ultrasonically treated for 30 minutes to form a 0.3-0.5 g / ml TiO2 suspension, solid paraffin is heated until it is completely dissolved, and alumina and the TiO2 suspension are added, mixed and stirred, and then cooled to form TiO2 / paraffin / alumina composite particles.

[0017] Preferably, the mass ratio of TiO2 nanoparticles to alumina in the TiO2 / paraffin wax / alumina composite particles is 1:0.03-0.07, and the mass of the paraffin wax accounts for 70-80% of the total weight of the composite particles.

[0018] Preferably, the carbon fiber mesh has a weight of 80-120 grams per square meter and a mesh size of 5mm×5mm-7mm×7mm;

[0019] Preferably, the TiO2 is in anatase phase, with a particle size of 10-30 nanometers and a purity of 99%, the phase transition temperature of paraffin is 22-30° C., and the particle size of alumina is 50 nanometers.

[0020] Preferably, the thickness of the UV curable resin layer in step A4 is about 0.2-0.5 mm to achieve rapid curing. After curing, the layer is cured at room temperature for 24 hours at a UV irradiation intensity of 100 mW / cm 2 , time is 3-5 minutes.

[0021] The present invention also provides a photocatalytic diatom purification functional decorative plate, which is prepared by the above-mentioned preparation method.

[0022] Porosity and surface treatment of diatomite substrate: Due to its natural high porosity, diatomite substrate provides good surface adsorption characteristics and large surface area, which is essential for the dispersion of effective carriers such as TiO2. Sanding the surface of diatomite substrate further increases the surface roughness, which helps the adhesion of subsequent materials and improves the contact opportunity and fixation effect of composite particles.

[0023] Application of heat-sensitive epoxy resin: Use heat-sensitive epoxy resin adhesive to form a bonding base on the diatomite substrate. Its characteristic is that the bonding performance can be adjusted under different temperature conditions. This property allows the decorative board to maintain the bonding between materials when the temperature fluctuates, preventing the expansion or contraction of the material caused by temperature changes.

[0024] Function of TiO2 / paraffin / alumina composite particles: TiO2 particles are not only evenly distributed on the diatomite substrate by compounding with paraffin and alumina, but also enhance the overall thermal stability and photocatalytic efficiency through the thermal phase change properties of paraffin and the high thermal conductivity of alumina. TiO2 is activated when exposed to light, generating strong oxidizing free radicals that effectively decompose pollutants in the air.

[0025] Structural reinforcement of carbon fiber mesh: The carbon fiber mesh is laid on the epoxy resin layer. As a reinforcing material, it significantly improves the mechanical strength and deformation resistance of the decorative board, allowing the board to withstand greater physical pressure while maintaining its lightweight characteristics.

[0026] Protective effect of UV curing resin: The UV curing resin applied in the final step provides a uniform protective film, which enhances the weather resistance of the decorative board, prevents the erosion of ultraviolet rays and moisture for a long time, and extends the service life of the decorative board while maintaining the surface finish and aesthetics.

[0027] The high porosity of the diatomite substrate provides sufficient surface area and adsorption sites for the heat-sensitive epoxy resin, which enables the epoxy resin to adhere more effectively and form a uniform bonding layer. In addition, the heat-sensitive nature of the epoxy resin allows it to adapt to the physical expansion or contraction of the diatomite when the temperature changes, keeping the integrity of the overall structure intact.

[0028] The introduction of the carbon fiber mesh not only provides mechanical support and enhances the compression and bending resistance of the decorative board, but also helps fix the TiO2 / paraffin / alumina composite particles and ensures that these particles are evenly distributed on the diatomite substrate. This uniform distribution is crucial for achieving effective photocatalytic activity because it ensures the light coverage and reaction efficiency of TiO2.

[0029] The photocatalytic activity of TiO2 can decompose harmful chemicals under light, while the phase change properties of paraffin and the thermal conductivity of alumina work together to regulate and disperse the heat generated by the photocatalytic reaction, preventing heat concentration from damaging the board. The UV-curable resin not only provides the necessary surface protection to prevent erosion by environmental factors such as moisture and UV radiation, but also maintains the structural stability of the composite particles, thereby maintaining the photocatalytic efficiency for a long time.

[0030] Beneficial effects brought by the technical solution of the present invention:

[0031] By using carbon fiber mesh and heat-sensitive epoxy resin adhesive, the present invention significantly improves the uniform distribution and fixation of composite particles on the diatomite board. This improvement not only ensures the consistency of photocatalytic performance, but also enhances the mechanical strength of the board, making it more suitable for long-term use.

[0032] Heat-sensitive epoxy resins enable decorative panels to adapt to changes in ambient temperature, especially maintaining or enhancing bonding strength when the temperature rises, thereby optimizing the stability and durability of the decorative panels.

[0033] The use of UV curing resin as a weather-resistant protective layer effectively prevents damage from external factors such as UV radiation and moisture, increases the service life of the decorative board, and maintains long-term photocatalytic performance.

[0034] The carbon fiber mesh and aluminum oxide added to the structural design significantly improve the hardness and wear resistance of the composite material, enabling the decorative panel to withstand higher mechanical stresses and adapt to harsh environmental conditions.

[0035] The invention improves the activity of the photocatalyst and the air purification efficiency by optimizing the TiO2 distribution, effectively decomposes harmful chemicals in the indoor air, and improves the air quality of the living and working environment.

[0036] By integrating alumina with good thermal conductivity, the present invention enhances the phase change effect of paraffin and the photocatalytic efficiency of TiO2, thereby improving the thermal efficiency and purification performance of the decorative board while maintaining its thermal stability.

[0037] These technological improvements provide obvious performance advantages, making the photocatalytic purification diatom functional decorative panels show high environmental adaptability, durability and functionality in the modern building materials market. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0039] Example 1

[0040] 1) Preparation of diatomaceous earth substrate: diatomaceous earth powder: 90 parts, cellulose binder: 10 parts.

[0041] Mixing and forming: mixing the above mixture with 60% of its total weight of water to obtain a wet mixture;

[0042] Pour the wet mixture into a mold measuring 200mm x 300mm with a mold thickness of 10mm;

[0043] The mixture was compacted using a press at a pressure of 5 MPa and the pressure was maintained for 5 minutes.

[0044] Drying treatment: Dry the formed sheet at room temperature until the surface is no longer wet;

[0045] The samples were transferred to an oven and dried at 50°C for 24 hours to completely remove moisture.

[0046] 2) Apply heat-sensitive epoxy resin:

[0047] Epoxy resin preparation: Epoxy resin (bisphenol A type) and acetone were mixed at a concentration of 4.5 g / ml;

[0048] Add 5% poly (N-isopropylacrylamide) (PNIPAM) and 1% diphenyl disulfide (DMPA) to the epoxy resin-acetone mixture and continue stirring until completely dissolved and evenly distributed;

[0049] The degassing treatment was carried out in a vacuum degassing machine for 30 minutes.

[0050] Coating treatment: The prepared heat-sensitive epoxy resin adhesive is evenly coated on the sandpaper-polished diatomaceous earth substrate with a thickness of 0.5 mm.

[0051] 3) Application of carbon fiber mesh and composite particles

[0052] Laying the carbon fiber mesh: The carbon fiber mesh (weight 100 g per square meter, mesh size 5 mm×5 mm) is laid flat on the uncured epoxy resin layer.

[0053] Preparation and application of composite particles: TiO2 nanoparticles (anatase phase, particle size 20 nm, purity 99%) were dispersed in anhydrous ethanol and then ultrasonically treated for 30 minutes to form a 0.4 g / ml TiO2 suspension;

[0054] Solid paraffin (phase transition temperature 28° C.) is heated until completely dissolved, and alumina (particle size 50 nanometers) and TiO2 suspension are added, and the mass ratio of TiO2 to alumina is 1:0.05, ensuring that the mass of paraffin accounts for 75% of the total weight of the composite particles, and the mixture is cooled after mixing and stirring to form TiO2 / paraffin / alumina composite particles;

[0055] Spread the composite particles on the carbon fiber mesh and compact them with a roller.

[0056] 4) Application of UV curing resin

[0057] Coating and curing: Coat a layer of UV curing resin (thickness 0.3 mm) on the treated plate.

[0058] Use UV lamp (irradiation intensity 100mW / cm 2 ) Curing for 3 minutes, and then continue to cure at room temperature for 24 hours.

[0059] Example 2

[0060] A photocatalytic purification diatomite functional decorative plate was prepared according to the same preparation method as in Example 1, except that the diatomite powder was 80 parts and the cellulose was 20 parts.

[0061] Example 3

[0062] A photocatalytic purification diatomite functional decorative plate was prepared according to the same preparation method as in Example 1, except that the content of poly N-isopropylacrylamide (PNIPAM) was 4%.

[0063] Example 4

[0064] A photocatalytic purification diatomite functional decorative plate was prepared according to the same preparation method as in Example 1, except that the content of poly N-isopropylacrylamide (PNIPAM) was 6%.

[0065] Example 5

[0066] A photocatalytic purification diatomite functional decorative plate was prepared according to the same preparation method as in Example 1, except that the content of diphenyl disulfide (DMPA) was 0.8%.

[0067] Example 6

[0068] A photocatalytic purification diatomite functional decorative plate was prepared according to the same preparation method as in Example 1, except that the content of diphenyl disulfide (DMPA) was 1.2%.

[0069] Example 7

[0070] A photocatalytic purification diatomite functional decorative plate was prepared according to the same preparation method as in Example 1, except that the mass ratio of TiO2 nanoparticles to alumina was 1:0.03, and the mass of paraffin accounted for 70% of the total weight of the composite particles.

[0071] Example 8

[0072] A photocatalytic purification diatomite functional decorative plate was prepared according to the same preparation method as in Example 1, except that the mass ratio of TiO2 nanoparticles to alumina was 1:0.07, and the mass of paraffin accounted for 80% of the total weight of the composite particles.

[0073] Example 9

[0074] A photocatalytic purification diatomite functional decorative plate was prepared according to the same preparation method as in Example 1, except that the carbon fiber mesh weighed 80 grams per square meter and had a mesh size of 7 mm×7 mm.

[0075] Example 10

[0076] A photocatalytic purification diatomite functional decorative plate was prepared according to the same preparation method as in Example 1, except that the thickness of the UV curing resin layer was about 0.5 mm.

[0077] Embodiment 11:

[0078] 1) Prepare diatomite substrate: diatomite powder: 80 parts, cellulose binder: 20 parts. Mix the above mixture with 50% of its total weight of water to obtain a wet mixture; pour the wet mixture into a mold with a size of 200mm x 300mm and a mold thickness of 5 mm; use a press to compact the mixture at a pressure of 5MPa and maintain the pressure for 5 minutes. Drying treatment: Dry the formed plate at room temperature until the surface is no longer wet; transfer it to an oven and dry it at 50°C for 24 hours to completely remove moisture.

[0079] 2) Coating with heat-sensitive epoxy resin: epoxy resin (bisphenol A type) and acetone are mixed at a concentration of 4g / ml; 4% poly N-isopropylacrylamide (PNIPAM) and 0.8% diphenyl disulfide (DMPA) are added to the epoxy resin-acetone mixture, and stirring is continued until it is completely dissolved and evenly distributed; degassing treatment is carried out in a vacuum degassing machine for 30 minutes. Coating treatment: The prepared heat-sensitive epoxy resin adhesive is evenly coated on the sandpaper-polished diatomaceous earth substrate with a thickness of 0.5mm.

[0080] 3) Application of carbon fiber mesh and composite particles: Laying carbon fiber mesh: The carbon fiber mesh (weight 80 grams per square meter, mesh size 5mm×5mm) is laid flat on the uncured epoxy resin layer. Preparation and application of composite particles: Use anhydrous ethanol to disperse TiO2 nanoparticles (rutile phase, particle size 10 nanometers, purity 99%) and then ultrasonically treat for 30 minutes to form a 0.3g / ml TiO2 suspension; Heat solid paraffin (phase transition temperature 22°C) until completely dissolved, and add alumina (particle size 50 nanometers) and TiO2 suspension, mix with a mass ratio of TiO2 to alumina of 1:0.03, ensure that the mass of paraffin accounts for 70% of the total weight of the composite particles, mix and stir, and cool to form TiO2 / paraffin / alumina composite particles; Sprinkle the composite particles on the carbon fiber mesh and compact them with a roller.

[0081] 4) Application of UV curing resin: Coating and curing: Coat a layer of UV curing resin (thickness 0.2 mm) on the treated plate. Use UV lamp (irradiation intensity 100mW / cm 2 ) Curing for 3 minutes, and then continue to cure at room temperature for 24 hours.

[0082] Embodiment 12:

[0083] 1) Prepare diatomite substrate: diatomite powder: 90 parts, cellulose binder: 10 parts. Mix the above mixture with 60% of its total weight of water to obtain a wet mixture; pour the wet mixture into a mold with a size of 200mm x 300mm and a mold thickness of 10 mm; use a press to compact the mixture at a pressure of 5MPa and maintain the pressure for 5 minutes. Drying treatment: Dry the formed plate at room temperature until the surface is no longer wet; transfer it to an oven and dry it at 50°C for 24 hours to completely remove moisture.

[0084] 2) Coating with heat-sensitive epoxy resin: epoxy resin (bisphenol A type) and acetone are mixed at a concentration of 6 g / ml; 6% poly N-isopropylacrylamide (PNIPAM) and 1.2% diphenyl disulfide (DMPA) are added to the epoxy resin-acetone mixture, and stirred continuously until completely dissolved and evenly distributed; degassing treatment is performed in a vacuum degassing machine for 30 minutes. Coating treatment: The prepared heat-sensitive epoxy resin adhesive is evenly coated on the sandpaper-polished diatomaceous earth substrate with a thickness of 0.5 mm.

[0085] 3) Application of carbon fiber mesh and composite particles: Laying carbon fiber mesh: The carbon fiber mesh (weight 120 grams per square meter, mesh size 7mm×7mm) is laid flat on the uncured epoxy resin layer. Preparation and application of composite particles: Use anhydrous ethanol to disperse TiO2 nanoparticles (rutile phase, particle size 30 nanometers, purity 99%) and then ultrasonically treat for 30 minutes to form a 0.5g / ml TiO2 suspension; Heat solid paraffin (phase transition temperature 30°C) until completely dissolved, and add alumina (particle size 50 nanometers) and TiO2 suspension, mix with a mass ratio of TiO2 to alumina of 1:0.07, ensure that the mass of paraffin accounts for 80% of the total weight of the composite particles, mix and stir, and cool to form TiO2 / paraffin / alumina composite particles; Sprinkle the composite particles on the carbon fiber mesh and compact them with a roller.

[0086] 4) Application of UV curing resin: Coating and curing: Coat a layer of UV curing resin (thickness 0.5 mm) on the treated plate. Use UV lamp (irradiation intensity 100mW / cm 2 ) Curing for 5 minutes, and then continue to cure at room temperature for 24 hours.

[0087] Comparative Example 1

[0088] A photocatalytic purification diatomite functional decorative board was prepared according to the same preparation method as in Example 1, except that the carbon fiber mesh was not laid, and the composite particles were directly spread on the heat-sensitive epoxy resin and then compacted.

[0089] Comparative Example 2

[0090] A photocatalytic purification diatomite functional decorative board was prepared according to the same preparation method as in Example 1, except that a different resin was used instead of a heat-sensitive epoxy resin.

[0091] Comparative Example 3

[0092] A photocatalytic purification diatomite functional decorative plate was prepared according to the same preparation method as in Example 1, except that no aluminum oxide was added.

[0093] Comparative Example 4

[0094] A photocatalytic purification diatomite functional decorative plate was prepared according to the same preparation method as in Example 1, except that no UV curing resin protective layer was added.

[0095] Comparative Example 5

[0096] A photocatalytic purification diatomite functional decorative plate was prepared according to the same preparation method as in Example 1, except that no solid paraffin and aluminum oxide were added.

[0097] Experimental test:

[0098] 1. Temperature response performance test

[0099] Test method:

[0100] Standard: ISO 9142, Adhesives – Effects of environmental conditions on adhesive properties.

[0101] Steps: Place the decorative board in different temperature environments (5℃, 20℃, 40℃) and expose it in each environment for 24 hours. Test the strength after each environment using a tensile testing machine.

[0102] 2. Mechanical strength and environmental adaptability test

[0103] Test method: GB / T 17657-2013, Test methods for wood panels and veneer wood panels.

[0104] Steps: Prepare sample plates; perform bending strength tests; record test results under different environmental conditions (humidity, temperature).

[0105] 3. Air purification efficiency test

[0106] Test method: ISO 22197-1, Method for determining the photocatalytic activity of building material surfaces.

[0107] Steps: Place decorative board samples in a closed test room. Release standard concentrations of organic pollutants (formaldehyde, benzene) into the room. Test the changes in pollutant concentrations in the air under lighting conditions and record the data before and after TiO2 activation.

[0108] Calculate the purification efficiency:

[0109] Purification efficiency (%) = (concentration before illumination - concentration after illumination) × 100 / concentration before illumination

[0110] 4. Thermal management and thermal conductivity test

[0111] Test Method: ASTM E1461, Thermal Diffusivity by the Transient Plane Source Technique.

[0112] Procedure: Prepare samples of different formulations. Measure the thermal conductivity and thermal diffusivity of each sample.

[0113] Compare and analyze the data differences before and after adding alumina to verify the effect of thermal management.

[0114] Table 1 Temperature corresponding test table

[0115]

[0116] Example 1 shows the best temperature response performance, with purification efficiency close to or exceeding 90% under all temperature conditions. This shows the effect of heat-sensitive epoxy resin and optimized composite material formulation, ensuring stable bonding and long-lasting performance at different temperatures.

[0117] Although the performance of Examples 2-10 is slightly lower than that of Example 1, it still shows that by adjusting the ratio of diatomaceous earth to cellulose, the content of PNIPAM and DMPA, and other factors, good performance can be maintained to a certain extent. The effects of these changes on the bonding strength and thermal sensitivity are significant, but not as good as those shown in Example 1.

[0118] The comparative examples show significantly lower performance, especially when no carbon fiber mesh is used and when a different resin is used, where performance drops significantly. This emphasizes the importance of carbon fiber mesh and specific resin selection in maintaining the performance of the trim panel.

[0119] Table 2 Air purification efficiency test

[0120] Test items Purification efficiency (%) Formaldehyde Purification efficiency (%) benzene Example 1 82.7% 79.3% Example 2 70.2% 68.9% Example 3 65.4% 63.1% Example 4 67.5% 65.2% Example 5 60.3% 58.4% Example 6 61.8% 59.9% Example 7 76.5% 74.2% Example 8 77.4% 75.1% Example 9 71.3% 69.8% Example 10 65.9% 64.0% Comparative Example 1 55.6% 53.7% Comparative Example 2 50.4% 48.6% Comparative Example 3 54.3% 52.5% Comparative Example 5 48.9% 47.1%

[0121] Example 1 showed the highest air purification efficiency, with purification rates of formaldehyde and benzene reaching 82.7% and 79.3%, respectively. This proves that the components used in the preparation process (high ratio of TiO2 to alumina, structural optimization of carbon fiber mesh) and the optimized formula of epoxy resin play a significant role in improving photocatalytic activity and mechanical strength.

[0122] Examples 7 and 8, in which the ratio of TiO2 to alumina was varied, also showed higher purification efficiencies, which emphasizes the role of alumina in improving the uniformity of TiO2 distribution and photocatalytic efficiency.

[0123] Except for Examples 7 and 8, although the purification efficiency of Examples 2-10 is lower, it is still significantly higher than that of the comparative example, which shows that even a slight adjustment of the formula can have a positive effect on the functional performance.

[0124] The comparative examples showed relatively low purification efficiency, especially comparative examples 2 and 5, in which no specific epoxy resin was used or key components (such as alumina or paraffin) were removed, highlighting the importance of these components in maintaining the performance of the board.

[0125] Table 3 Thermal management and thermal conductivity test

[0126] Test items Thermal conductivity (W / m·K) <![CDATA[Thermal diffusivity (mm 2 / s)]]> Example 1 1.65 2.35 Example 7 1.38 1.90 Example 8 1.42 2.00 Example 9 1.28 1.70 Example 10 1.21 1.65 Comparative Example 3 0.95 1.25

[0127] Example 1 exhibits the highest thermal conductivity and thermal diffusivity, which are 1.65 W / m·K and 2.35 mm 2 / s, which shows the effectiveness of optimizing its composite material formula in improving thermal stability and thermal conductivity. The superior performance of Example 1 is attributed to its efficient component configuration and manufacturing process, especially the composite application of carbon fiber mesh and high concentration of TiO2 and alumina, which not only increases the thermal stability of the material, but also optimizes the photocatalytic activity.

[0128] Examples 7 and 8 have slightly lower thermal conductivity and thermal diffusivity, which may be due to the different ratios of TiO2 and alumina affecting thermal conductivity. Despite the decrease, the performance of these two examples is still better than the comparative example, indicating that even a small adjustment in the material ratio can significantly affect the performance.

[0129] The lower thermal conductivity and thermal diffusivity of Examples 9 and 10 may be due to the adjustment of the carbon fiber mesh density and the thickness of the UV-cured resin layer used in the structural design, which affects the overall thermal conductivity of the material.

[0130] Comparative Example 3 exhibits the lowest thermal conductivity and thermal diffusivity, which confirms the key role of alumina in enhancing thermal conductivity. The lack of alumina results in a significant decrease in the thermal management capabilities of the composite.

[0131] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a photocatalytic purification diatomite functional decorative board, characterized in that: The method comprises the following steps: A1 provides a diatomaceous earth substrate and polishes the surface with sandpaper. The preparation method of the diatomite substrate comprises: mixing 80-90 parts of diatomite powder with 10-20 parts of cellulose, gradually adding 50-60% of water by weight of the total weight of the mixture to the mixture to obtain a wet mixture, pouring the wet mixture into a mold with a thickness of 5-10 mm, using a press to compact the mixture at a pressure of 5 MPa, maintaining the pressure for 5 minutes, drying the formed plate at room temperature until the surface is no longer wet, and then transferring it to an oven to remove moisture; A2 evenly coats a layer of heat-sensitive epoxy resin adhesive on the diatomite substrate. The preparation method of the heat-sensitive epoxy resin is as follows: the epoxy resin is mixed with acetone at a concentration of 4-6 g / ml, poly N-isopropylacrylamide (PNIPAM) is added to the mixture of the epoxy resin and acetone at a content of 4-6% by mass of the mixture, and the mixture is continuously stirred until it is completely dissolved and evenly distributed, and 0.8-1.2% by mass of diphenyl disulfide (DMPA) is added to the mixture, and the stirring is continued to ensure that the mixture is completely evenly distributed, and the mixture is placed in a vacuum degassing machine to remove all bubbles in the mixture; A3 lays the carbon fiber mesh on the uncured heat-sensitive epoxy resin layer, then spreads the TiO2 / paraffin / alumina composite particles, compacts them with a roller, and uses an oven to accelerate the curing. Preparation method of TiO2 / paraffin / alumina composite particles: using anhydrous ethanol to disperse TiO2 nanoparticles and then perform ultrasonic treatment to form a 0.3-0.5g / ml TiO2 suspension, heating solid paraffin until it is completely dissolved, adding alumina and the TiO2 suspension, mixing and stirring, and then cooling to form TiO2 / paraffin / alumina composite particles, wherein the mass ratio of TiO2 nanoparticles to alumina in the TiO2 / paraffin / alumina composite particles is 1:0.03-0.07, and the mass of the paraffin accounts for 70-80% of the total weight of the composite particles; A4: coating the plate in step A3 with UV curable resin as a weather-resistant protective layer, and curing it using a UV lamp.

2. The method for preparing the photocatalytic purification diatomite functional decorative board according to claim 1, characterized in that: The epoxy resin is bisphenol A type epoxy resin.

3. The method for preparing the photocatalytic purification diatomite functional decorative board according to claim 1, characterized in that: The carbon fiber mesh has a weight of 80-120 grams per square meter and a mesh size of 5mm×5mm-7mm×7mm.

4. The method for preparing the photocatalytic purification diatomite functional decorative board according to claim 1, characterized in that: The TiO2 is in anatase phase with a particle size of 10-30 nanometers, the phase transition temperature of paraffin is 22-30° C., and the particle size of aluminum oxide is 50 nanometers.

5. The method for preparing the photocatalytic purification diatomite functional decorative board according to claim 1, characterized in that: The thickness of the UV curable resin layer in step A4 is 0.2-0.5 mm to achieve rapid curing, and curing is continued at room temperature after curing is completed.

6. A photocatalytic purification diatomite functional decorative board, characterized in that: The decorative panel is prepared by any one of the preparation methods described in claims 1-5.

Citation Information

Patent Citations

  • Gypsum plaster board, preparation method and use method thereof

    CN105587084A

  • Diatom plate with photocatalysis function and production process thereof

    CN106747162A

Cited By

  • Bamboo and wood board surface applying equipment for photocatalytic active material

    CN120038073A

  • A device for applying a photocatalytic active material to the surface of bamboo-wood boards

    CN120038073B